(3aVd GdbjGe HGdSdWfI GdTQjaIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdTCf agPG cJGH CdaJg aj aVd GdbjGe HGdSdWfI GdTQjaI hLeYJ ajg eG hQO aj Pdc ef GdCMGOjK hGdBKGQ heG CYO ef GdCLQ Ydi GdbjGe HgPG GdefUH GdTQjas
(3BNQgG (B:s
(3hCNQL GdHjgbj aj TYH GdEjeGf Yf EjGS Hf eYGhjI bGd dGHO ddfGS ef KdGKI CTjGA dGHO dge ef Cf JCeQg SHjdge hjNJGQ HMcege MJi jYOd GdMce ajge hCf JbGe dge GdKZhQ GdJj Hjfge hHjf YOhge hGdMeO ddgs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B1\14s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdSjGSI hGdGLJeGYs